A Case Report on 13q12.3 Microdeletion Syndrome Caused by HMGB1 Haploinsufficiency - Ting Wen; Brian J. Shayota; Lauren Wallace; Coumarane Mani; Neal Davis; Jian Zhao (Case Reports in Genetics)
Heterozygous microdeletions at 13q12.3 are associated with a rare genetic disorder, 13q12.3 microdeletion syndrome, characterized by intellectual disability, microcephaly, development delay, facial dysmorphisms, atopy, and obesity. Reported 13q12.3 microdeletions vary in size and typically encompass multiple genes. Previous studies have defined a minimal overlap region of 13q12.3 microdeletions and suggested that most of the phenotype associated with the 13q12.3 microdeletion syndrome could be attributed to the loss of the high mobility group box 1 (HMGB1) gene within the overlap region. Here, we report a pediatric patient who had typical phenotypic features of 13q12.3 microdeletion syndrome, including motor and moderate speech developmental delays, microcephaly, and severe atopy, along with anxiety and aggressive behaviors. Trio-based microarray analysis identified a 62-kb apparently de novo heterozygous deletion at 13q12.3 in the proband, fully encompassing all coding exons of the HMGB1 gene yet not affecting any other neighboring genes. This case report presents a rare HMGB1 single-gene deletion in a patient with classic features of 13q12.3 microdeletion syndrome, allowing a better delineation of clinical phenotypes associated with the loss of HMGB1. Our findings, together with previous reports, strongly support the pathogenic role of HMGB1 haploinsufficiency in the 13q12.3 microdeletion syndrome.